A dual-emission nano-rod MOF equipped with carbon dots for visual detection of doxycycline and sensitive sensing of MnO4−. Issue 9 (25th January 2018) - Fu, Xin; Lv, Rui; Su, Jian; Li, Hui; Yang, Boyi; Gu, Wen; Liu, Xin
Abstract : A dual-emission hybrid material could detect doxycycline and MnO4 − sensitively. Test paper was regarded initially as a tool for doxycycline visual detection. A lower LOD of MnO4 − showed that carbon dots can accelerate quenching speed of MOF(Eu). Abstract : Herein, ethanediamine-modified carbon dots (CDs) were encapsulated into luminescent MOF(Eu), which was designed for a dual-emission hybrid material (CDs@MOF(Eu)) with diverse fluorescence applications. This material exhibited high selectivity and sensitivity towards doxycycline. With an increasing concentration of doxycycline, the blue light emission of CDs could be quenched, whereas the red light emission of MOF(Eu) was enhanced. In view of this result, more convenient "test paper" was used first as a new tool for doxycycline detection, the colour of which turned from blue-purple to red as observed by the naked eyes under 365 nm UV-irradiation. This hybrid material also was a probe for sensing MnO4 − with a low limit of detection and good anti-interference performance. We propose that CDs can improve detection sensitivity compared with the original MOF(Eu). The possible sensing mechanism was discussed in detail. Importantly, the feasibility of this composite for sensing doxycycline in a simulated biological system and sensing MnO4 − in tap water was investigated.